Superexchange coupling in hexahalosalts of elements in the third transition series. - Bhiwandker, N. C. (University of Ottawa (Canada), 1960)
Theories of magnetism with special reference to Ligand field and Kotani's theory are discussed. An investigation of the applicability of Kotani's theory to the complexes of heavy transition elements is described. Magnetic susceptibilities of potassium chloroplatinate, potassium chloroiridate, potassium chloroosmate, potassium bromoosmate, potassium chlororhenate and potassium hydroxy-pentachlorotungstate were measured over a temperature range 90°K to 300°K. It is shown that the complexes, with the exception of potassium chlororhenate, do not obey the Curie-Weiss law. Measurements have been carried out on the paramagnetic salts diluted with isomorphous diamagnetic potassium chloroplatinate and potassium bromoplatinate over a temperature range 90°K to 300°K. It is shown that the magnetic moments of the paramagnetic ions increase as their concentration in the solid solutions decreases. This shows that there is a considerable interaction between paramagnetic ions in crystals of the pure substances and that this interaction is decreased by the inclusion of diamagnetic ions in the crystals, giving a higher value for the magnetic moment. Although pure substances do not follow Kotani's theory, on dissolution in an isomorphous diamagnetic salt there is a trend towards normal behavior and at infinite dilution of the paramagnetic for normal behavior is attained. Thus it has been shown that there is appreciable orbital contribution to the magnetic moment of Ir (IV) ion and that a value of the right order of magnitude for the coupling constant could be calculated from the magnetic susceptibility measurements for ions with dE4 configuration.
Keywords: Chemistry, Inorganic.